Field notes contributed by Tom Stone, fall 1977 - Stone, Tomet al (1977)
List of birds and locations contributed by Tom Stone. The field notes include a detailed description of two nesting Swainson's Hawks and a late observation of a Ruby-throated Hummingbird. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed